Valkyrie - Singer, Bryan; McQuarrie, Christopher; Adler, Gilbert; Alexander, Nathan; Cruise, Tom; Metro-Goldwyn-Mayer Pictures; United Artists (Firm) (Los Angeles, CA : MGM Home Entertainment, 2009)
Based on the incredible true story of Colonel Claus von Stauffenberg and his ingenious assassination plot targeting Adolf Hitler, this engrossing thriller reenacts the daring operation to eliminate one of the most evil tyrants the world has ever known
Title from title screen
Director of photography, Newton Thomas Sigel ; editor, John Ottman ; music, John Ottman
Cast: Tom Cruise, Kenneth Branagh, Bill Nighy, Tom Wilkinson, Carice van Houten, Thomas Kretschmann, Terence Stamp
DVD format
Dolby digital 5.1
Keywords: Hitler, Adolf, -- 1889-1945 -- Assassination attempt, 1944 (July 20) -- Drama; Schenk von Stauffenberg, Klaus Philipp, -- Graf, -- 1907-1944 -- Drama; Operation Valkyrie, 1944 -- Drama; Anti-Nazi movement -- Germany -- Drama